Each cell counts: Hematopoiesis and immunity research in the era of single cell genomics. Issue 1 (February 2015) - Jaitin, Diego Adhemar; Keren-Shaul, Hadas; Elefant, Naama; Amit, Ido
Highlights Single-cell genomics opens a new era in hematopoiesis and immunity research. Development of massively parallel single cell genomic technologies. Single-cell genomic approaches are instrumental to untangling hematopoiesis and the immune system complexity. Applying single-cell genomics to immune-related diseases will allow for better diagnostics, prognosis and therapeutics.